Oxidative dehydrogenation of ethane with carbon dioxide over iron-nickel nano-alloys supported on metal oxide overlayers - Raseale, Shaine (Department of Chemical Engineering, 2023)
The CO2-mediated oxidative dehydrogenation of ethane (CO2-ODHE) is one of the promising alternative routes for simultaneous conversion of ethane and the greenhouse gas (GHG) CO2 into high-demand monomers: ethylene and CO [1,2]. It has been extensively investigated on oxide catalysts with those based on Cr, V and Ga exhibiting high yields and selectivity for ethylene but those deactivate rapidly [3–12]. The reaction follows a Mars van Krevelen mechanism where the oxide is partially reduced upon ethane activation and subsequently re-oxidized upon CO2- activation [13]. Thus, suitable redox properties as well as Lewis acidity of metal oxides are some essential properties governing catalytic performance [13–15]. The lower stability of these materials is linked to their failure to act as multifunctional catalysts that can prevent carbon buildup via the dissociation of CO2 while co-activating ethane. Promoters such as Fe-based oxides have been studied to enhance the CO2-activation functionality and stability of the oxides [5]. A Density Functional Theory (DFT) study suggested that bimetallic alloys can have superior activity for CO2-activation compared to their monometallic counterparts [16]. Therefore, bimetallic alloys in conjunction with metal oxides may serve as stable bifunctional CO2-ODHE catalysts with enhanced CO2-activation ability. Improved CO2-activation can boost the re-oxidation rate of the metal oxide via a spillover-type mechanism and aid in coke removal via the reverse Boudouard reaction [5,11]. Recent studies have already demonstrated this experimentally with a series of supported FexNiy catalysts prepared via impregnation which, depending on Fe : Ni ratio and support, can promote either the CO2-ODHE or the competing ethane dry-reforming (DRE) reactions with enhanced CO2-activation [17,18,18–20]. However, composition and crystallite size uniformity are difficult to attain via impregnation as Ni and Fe oxide phases present in parallel make it challenging to extract the influence of the FexNiy alloy metallic composition [21]. This work aims to synthesize catalytically active metal oxide overlayers of a comparable pore structure, anchor FexNiy nano-alloys of uniform composition with Fe and Ni in close proximity and investigate the combined effect of the overlayer support's acidity/reducibility and alloy composition on the catalytic performance under CO2-ODHE conditions. The close proximity of Fe and Ni in the alloy is introduced by the use of oxidic Ni-ferrite spinel structures as precursors of the alloy which is formed upon their reduction in H2 atmosphere and was found to exist as a mixture of a bcc and an fcc phases depending on Fe : Ni ratio. A higher Fe content in the alloy increases the fraction of the bcc phase as confirmed via H2-TPR studies in in situ XRD. In situ XRD temperature-programmed CO2-activation studies also revealed that CO2 is only able to react with the bcc phase of the alloy which is re-oxidised into the oxidic Niferrite spinel while the fcc phase is stable against re-oxidation. While they deactivate rapidly due to a limited re-oxidation and coking caused by insufficient CO2- activation, the bare metal oxide overlayers exhibit an initial activity that reduces with a decrease of the surface acid site strength until a minimum is reached and then slightly increases with increasing basicity under CO2-ODHE conditions. Their catalytic stability increases with weakening of the acid site strength. Decreasing the overlayer acidity enhances the CO2-ODHE/DD (DD : direct dehydrogenation) activity resulting in increased ethylene and decreased CO selectivity. Spent catalyst analysis revealed the formation of surface carbonaceous deposits suspected to cause catalyst deactivation. Increasing the concentration of CO2 in the feed results in improved and sustained CO2-activation which enhances the reverse Boudouard reaction and improves the catalyst stability by reducing carbon deposition while reducing ethylene and increasing CO selectivity. Deposition of the FexNiy nano-alloys of Fe : Ni atomic ratios of 1, 3 and 5 on the reducible and acidic CrOx@Al2O3 results in an alloy composition-dependent catalyst performance, while the alloys are essentially inactive over the less acidic and unreducible ZrOx@Al2O3. This clearly confirms a bifunctional character of these materials and reveals that their catalytic performance depends on both the overlayer reducibility/acidity and the metallic composition of the alloy. Over CrOx@Al2O3, the alloy enhances the CO2-activation functionality with increasing Ni-content boosting the overall activity and stability of the catalyst. However, with increasing Ni-content, the CO selectivity increases while ethylene selectivity reduces due to the suppressed CO2-ODHE/DD activity and promotion of the competing DRE reaction. The target CO2-ODHE/DD reaction activity is maximal at an overall Fe : Ni atomic ratio of 5, about 10% at a ratio of 3 and completely suppressed at a ratio of 1. Spent catalyst analysis revealed formation of surface carbonaceous deposits and that the bcc phase of the alloy is re-oxidised into the Ni-ferrite oxidic spinel phase while the fcc phase of the alloy is stable against re-oxidation during the reaction. Increased CO2 concentration in the feed has similar effects as described for the bare overlayers. Deposition the Fe3Ni1 and Fe5Ni1 nano-alloys on GaOx@Al2O3, VOx@Al2O3, SmOx@Al2O3 and TiOx@Al2O3 revealed that despite the alloy composition, a predominant DRE activity is observed over the highly acidic and reducible VOx@Al2O3. While CrOx@Al2O3 and GaOx@Al2O3 show a similar performance when tested bare, the addition of the Fe3Ni1 and Fe3Ni1 alloys on the GaOx@Al2O3 overlayer results in a high CO2-ODHE/DD activity with stability decreasing with increasing Fe-content. Over TiOx@Al2O3, the Fe3Ni1 nano-alloy exhibits a similar behaviour as over GaOx@Al2O3 while higher iron contents resulted in an inactive catalyst. Over SmOx@Al2O3 no alloy composition yields appreciable catalytic activity. The CO2-ODHE/DD behaviour of Fe3Ni1/GaOx@Al2O3 is in stark contrast to the high DRE activity over Fe3Ni1/CrOx@Al2O3 emphasising that a specific alloy composition exists for each overlayer to yield a stable and dominating CO2-ODHE/DD or DRE activity. For a high and stable CO2-ODHE/DD activity, the optimum in atomic Fe : Ni ratio was found to be between the 3 and 5 at intermediate-intermittent overlayer acidity. In addition to improving stability, increased CO2 concentration in the feed was found to significantly accelerate an observed active site re-construction during reaction which results in formation of more CO2-ODHE/DD sites.